(untitled) (Nueva Epoca, 2025)
This paper examines the limits of civil liability arising from the interrelation of contracts, following the incorporation into the Argentine Civil and Commercial Code (arts. 1073–1075) of a specific regulation governing the consequences of contractual connectedness. It analyzes chains and groups of contracts, their legal effects, and the scope of direct actions and joint liability. The article argues that, while such interrelation justifies an integrated framework for connected contracts, the excessive extension of joint liability by case law is inconsistent with the restrictive approach established by law. For that reason, the author proposes resorting to the Argentine legal figure of “concurrent obligations” as a more consistent alternative.